Boosting competence-orientation in undergraduate medical education – A web-based tool linking curricular mapping and visual analytics. (3rd April 2019) - Fritze, Olaf; Lammerding-Koeppel, Maria; Boeker, Martin; Narciss, Elisabeth; Wosnik, Annette; Zipfel, Stephan; Griewatz, Jan
Abstract: Objectives: Transition to competency-based medical education is a highly challenging endeavor. Students, teachers and institutions need curricular transparency for understanding the build-up of competencies in terms of coverage, sequence and consistence of learning objectives and assessment. The project aim was to develop and implement a web-based interactive platform for curriculum mapping, diagnostics, and development. The tool should be transferable to other faculties and allow description and visualization of medical curricula in comparison to given national competency-based standards. Methods: In a design-based multi-center approach, four German medical faculties cooperated and developed a standardized, common mapping tool (MER lin database). Implemented are techniques for big data handling and visual analytics. Results: The platform profile is adapted closely to user needs. Intuitive data entry and comfortable quality maintenance support teacher engagement. Individual navigation for curricular diagnostics is guided by practice-oriented questions. Sophisticated, easy-understandable visualizations show curricular strengths and weaknesses. Transparency in contributing departments facilitates goal-oriented dialogs. Currently, 14 of 38 German faculties use the platform. Conclusions: In view of huge amounts of data and complex curricular structures, the MER lin database facilitates effective curriculum mapping, goal-oriented curriculum development, comparison to national competency-based standards, effective data sharing and benchmarking across faculties with different curriculum management systems.